Strategic Procurement Practices and Procurement Performance: A Practical Investigation of the Commercial Banks in Quetta - Sadiqeen, Zain Ul; Ullah, Safi; Bano, Safia (Annals of Human and Social Sciences, 2023)
The study examines the key procurement strategies employed by banks, such as supplier evaluations, contract negotiations, and supplier performance metrics. The research also analyzes the impact of technology on procurement processes and how banks can collaborate with suppliers to improve performance and reduce costs. The study aims to provide insights into best practices for strategic procurement in commercial banks, including cost savings, increased supplier performance, and improved quality of goods and services. The findings of this research can help banks enhance their procurement processes, which can ultimately lead to increased profitability and customer satisfaction. Therefore, this study has been conducted to describe the vital role of procurement in the commercial banks of Quetta, Balochistan. This study involves procurement practices to know their best role in performing the various functions of the banks which includes the procurement process, establishment of the procurement plan, strategic procurement practices, supplier chain management, and procurement performance. The study was quantitative in nature. Non probability method in which convenience sampling technique was used to collect data via questionnaire from the commercial banks operating in Quetta. Furthermore, SMART PLS 4. Was used to analyses the data. The result of the study has proved that significant positive effect of relationships between strategic procurement and procurement performance. Furthermore, challenges related to procurement mediate the relationship between both constructs.